1973
DOI: 10.1111/j.1471-0528.1973.tb16050.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal 5‐hydroxytryptamine Levels in Late Pregnancy

Abstract: Summary The human fetus of 38 to 41 weeks' gestation has a whole blood 5‐hydroxytryptamine (5‐HT) concentration equivalent to the adult. It is suggested that the fetus in utero is capable of producing 5‐HT in sufficient amounts to account for the documented rise in placental 5‐HT concentration found in late pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…This amine also produces powerful contractions, greater than other agents, in human and animal umbilical or placental vessels (Dyer, 1970;Altura et al, 1972;Nair & Dyer, 1974;Tulenko, 1979;Mak et al, 1984;Maigaard et al, 1986). In addition, it has been demonstrated that the concentration of 5-HT in the maternal blood and blood present in umbilical vessels at term (vaginal delivery) is around 10-7M (in both cases measured in the whole blood) (O' Reilly & Loncin, 1967;Jones & Rowsell, 1973), i.e., similar to our EC50 values for 5-HT on chorionic vessels. It has been suggested that 5-HT may contribute to spasm and closure of the umbilical vessels after birth (Tulenko, 1979;Mak et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This amine also produces powerful contractions, greater than other agents, in human and animal umbilical or placental vessels (Dyer, 1970;Altura et al, 1972;Nair & Dyer, 1974;Tulenko, 1979;Mak et al, 1984;Maigaard et al, 1986). In addition, it has been demonstrated that the concentration of 5-HT in the maternal blood and blood present in umbilical vessels at term (vaginal delivery) is around 10-7M (in both cases measured in the whole blood) (O' Reilly & Loncin, 1967;Jones & Rowsell, 1973), i.e., similar to our EC50 values for 5-HT on chorionic vessels. It has been suggested that 5-HT may contribute to spasm and closure of the umbilical vessels after birth (Tulenko, 1979;Mak et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…This might trigger 5-HT release from uterine and placental stores and induce delivery (Koren et al, 1965), and contraction of placental vessels. The increase in placental 5-HT concentration is probably due to an augmentation in the production of 5-HT in the developing foetus, since the placenta appears to lack the ability to synthesize 5-HT (Jones & Rowsell, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of 5-HT have been reported at birth in maternal and placental circulation [25] , indicating a role for 5-HT in maintaining vascular tone at birth. In pre-eclampsia, Middelkoop et al [26] showed an increase in maternal circulation of 5-HT in pre-eclamptic patients, suggesting a role for 5-HT in the aetiology of pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin concentrations in rats increase in the hypothalamus, rhinencephalon, and mesencephalon during pregnancy (15). It is of interest that the fetus produces much of the serotonin observed in pregnancy (16); this perhaps suggests an evolutionary advantage to the inhibition of self-destructive behaviors by the mother.…”
Section: Discussionmentioning
confidence: 99%